Force From Filaments: The Role of the Cytoskeleton and Extracellular Matrix in the Gating of Mechanosensitive Channels - Chuang, Yu-Chia; Chen, Chih-Cheng (Frontiers in Cell and Developmental Biology, 2022)
The senses of proprioception, touch, hearing, and blood pressure on mechanosensitive ion channels that transduce mechanical stimuli with high sensitivity and speed. This conversion process is usually called mechanotransduction. From nematode MEC-4/10 to mammalian PIEZO1/2, mechanosensitive ion channels have evolved into several protein families that use variant gating models to convert different forms of mechanical force into electrical signals. In addition to the model of channel gating by stretching from lipid bilayers, another potent model is the opening of channels by force tethering: a membrane-bound channel is elastically tethered directly or indirectly between the cytoskeleton and the extracellular molecules, and the tethering molecules convey force to change the channel structure into an activation form. In general, the mechanical stimulation forces the extracellular structure to move relative to the cytoskeleton, deforming the most compliant component in the system that serves as a gating spring. Here we review recent studies focusing on the ion channel mechanically activated by a tethering force, the mechanotransduction-involved cytoskeletal protein, and the extracellular matrix. The mechanosensitive channel PIEZO2, DEG/ENaC family proteins such as acid-sensing ion channels, and transient receptor potential family members such as NompC are discussed. State-of-the-art techniques, such as polydimethylsiloxane indentation, the pillar array, and micropipette-guided ultrasound stimulation, which are beneficial tools for exploring the tether model, are also discussed.